PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN, KOMISARIS INDEPENDEN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Irene Delfiona Tanisa; Hexana Sri Lastanti (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This research was aimed for testing the effect of financial performance with liquidity and profitability as proxied, firm size, independent commissioners, and corporate social responsibility on tax aggressiveness in the manufacturing sector listed on Indonesia Stock Exchange (IDX). This research used quantitative data collected by using purposive sampling method with criteria as such as using the rupiah currency, having a positive profit, and listed on IDX in the period 2018-2020. The criteria resulted a sample of 72 companies that can be research using the multiple linear regression analysis method. The outcome of hypothesis in this research illustrated that profitability and company size partially have a positive significant effect on tax aggressiveness, while liquidity, independent commissioners, and corporate social responsibility did not have a significant effect on tax aggressiveness.